전북지역 제초제 저항성 논 잡초 발생분포 및 제초제 사용실태 - 이인용(In-Yong Lee); 김정곤(Chung-Kon Kim); 송영주(Young-Ju Song); 이덕렬(Deok-Ryeol Lee); 송영은(Young-Eun Song); 권석주(Seog-Ju Kwon); 조승현(Seung-Hyun Cho) (Weed & turfgrass science, 2014)
This study was conducted to obtain basis information for effective weed control by the fact-finding survey of herbicides use at farmer's level and distribution of herbicide resistant weeds in paddy field of Jeonbuk province, Korea. The distributions of major paddy field weeds and frequently used herbicide according to the survey were as follows. The dominant weeds in rice paddy field were Echinochloa crus-galli, Eleocharis kuroguwai, Scirpus juncoides, Monochoria vaginalis, etc.. Preferred herbicides widely used by farmers were ranked in the following order, early and middle treatment (48.0%), treatment before transplanting (36.7%) and foliar treatment (15.3%). The occurrence of herbicide-resistant weeds according to collected paddy soils was as follows. The occurring area of herbicide-resistant weeds was 24,413 ha, approximately 18.4% of rice cultivation area. Herbicide-resistant weeds were occurred in four species. The order of occurrence were Scirpus juncoides (39.0%) > Monochoria vaginalis (27.8%) > Echinochloa crus-galli (16.6%) and Cyperus difformis (16.6%). This information could be useful for estimation of future herbicide-resistant weed and establishment of herbicide-resistant weed control methods in Jeonbuk province, Korea. 전라북도 지역 논에서 발생되고 있는 저항성잡초와 문제 잡초의 발생 모니터링을 통하여 효율적인 논 잡초 방제기술을 확립하기 위한 기초자료로 활용하고자 시험을 수행하여 얻어진 결과는 다음과 같다. 전북지역 논에서의 잡초 발생 분포와 재배농가들이 선호하는 제초제 등을 설문조사한 결과, 우점초종은 피, 올방개, 올챙이고랭이, 물달개비 등이었으며 재배농가들이 선호하는 제초제는 초 중기처리 제초제(48.0%)>이앙전처리 제초제(36.7%)>경엽처리 제초제(15.3%) 순이었다. 논 토양조사에 의해 전북지역 제초제 저항성잡초 발생정도를 조사한 결과, 제초제 저항성잡초 발생면적은 총 재배면적의 18.4%인 24,413 ha 였으며 발생 초종은 4초종으로 올챙이고랭이(39.0%)>물달개비(27.8%)>강피(16.6%), 알방동사니(16.6%) 순으로 발생비율이 높았다. 이러한 정보를 이용하여 전북지역의 제초제 저항성잡초 발생을 예측하고 이에 맞는 제초제 저항성잡초 관리 방안을 수립할 수 있을 것으로 판단된다.